Acute neuromuscular, cardiovascular, and muscle oxygenation responses to low-intensity aerobic interval exercises with blood flow restriction - Lavigne, C.; Mons, V.; Grange, M.; Blain, G. M. (Experimental Physiology, 2024)
We investigated the influence of short- and long-interval cycling exercise with blood flow restriction (BFR) on neuromuscular fatigue, shear stress and muscle oxygenation, potent stimuli to BFR-training adaptations. During separate sessions, eight individuals performed short- (24 × 60 s/30 s; SI) or long-interval (12 × 120 s/60 s; LI) trials on a cycle ergometer, matched for total work. One leg exercised with (BFR-leg) and the other without (CTRL-leg) BFR. Quadriceps fatigue was quantified using pre- to post-interval changes in maximal voluntary contraction (MVC), potentiated twitch force (QT) and voluntary activation (VA). Shear rate was measured by Doppler ultrasound at cuff release post-intervals. Vastus lateralis tissue oxygenation was measured by near-infrared spectroscopy during exercise. Following the initial interval, significant (P < 0.05) declines in MVC and QT were found in both SI and LI, which were more pronounced in the BFR-leg, and accounted for approximately two-thirds of the total reduction at exercise termination. In the BFR-leg, reductions in MVC (-28 ± 15%), QT (-42 ± 17%), and VA (-15 ± 17%) were maximal at exercise termination and persisted up to 8 min post-exercise. Exercise-induced muscle deoxygenation was greater (P < 0.001) in the BFR-leg than CTRL-leg and perceived pain was more in LI than SI (P < 0.014). Cuff release triggered a significant (P < 0.001) shear rate increase which was consistent across trials. Exercise-induced neuromuscular fatigue in the BFR-leg exceeded that in the CTRL-leg and was predominantly of peripheral origin. BFR also resulted in diminished muscle oxygenation and elevated shear stress. Finally, short-interval trials resulted in comparable neuromuscular and haemodynamic responses with reduced perceived pain compared to long-intervals.